"Income vs. education" revisited – the roles of "family face" and gender in Chinese consumers' luxury consumption. Issue 4 (7th September 2020) - Mo, Tingting
Abstract : Purpose: The transgenerational influence of inherited family capital on consumers' luxury consumption has been studied recently in the mature luxury market. However, little research explores this topic in the emerging luxury market. In China's Confucian culture, "family face" as part of "family inheritance" has been conceptualized as a factor driving luxury consumption. However, this hypothesis has not been empirically tested. The current research, therefore, seeks to examine the impact of economic and cultural capital on Chinese consumers' luxury consumption within the family inheritance context and the roles that face concern and gender play to reveal the particularities of a specific emerging luxury market. Design/methodology/approach: A sample of 324 Chinese consumers was recruited in Shanghai. With the full sample, the author first assessed the effects of economic and educational capital (both personal and family sources) and face concern on luxury consumption using regression analyses. Next, the author conducted the regression analyses again by gender. Findings: Unlike trends in the mature luxury market, Chinese consumers' educational levels do not drive their luxury consumption, and the transgenerational influence of economic and cultural capital functions as a negative factor. Influenced by the patrilineal tradition, higher levels of luxury consumption to compensate for parents' lower income and educational levels and to enhance family face are found only in the male consumer group, but not in the female group. Originality/value: This research contributes to expanding the current understanding of emerging luxury markets and how the Confucian tradition influences Chinese consumers' luxury consumption through gender role norms.